2020
DOI: 10.4018/978-1-7998-0272-3.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Consumerism in Financial Institutions

Abstract: There has been a rise in the concept of ethical consumerism in various sectors of the economy. This chapter examines ethical consumerism in the Bahrain banking sector by analyzing customer surveys and annual reports from seven commercial banks. The findings show limited evidence of ethical consumerism in supply and demand. This chapter also documents challenges faced by banks and customers in ethical, social, and environmental decision making and operations. Finally, the results enhance the understanding of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Al Nasser & Muhammed (2013), found that Islamic bank customers were not completely satisfied with Islamic products even though more branches were opened by conventional banks operating in accordance with Islamic sharia principles. Abdulla (2020), also write "evidence on current practice by Islamic banks around the world indicates that the majority of financing operations are not based on equity. In contrast, Islamic banks have consistently favored the use of debt-based financing models".…”
Section: Spiritual Experience On Customer Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…Al Nasser & Muhammed (2013), found that Islamic bank customers were not completely satisfied with Islamic products even though more branches were opened by conventional banks operating in accordance with Islamic sharia principles. Abdulla (2020), also write "evidence on current practice by Islamic banks around the world indicates that the majority of financing operations are not based on equity. In contrast, Islamic banks have consistently favored the use of debt-based financing models".…”
Section: Spiritual Experience On Customer Loyaltymentioning
confidence: 99%
“…These banks imitate some of the worst banking practices of conventional financial institutions and do not serve the purposes of Islamic banking and finance" (Zaman, 2018). Abdulla (2020), write "evidence on current practice by Islamic banks around the world indicates that the majority of financing operations are not based on equity. In contrast, Islamic banks consistently prefer the use of debt-based financing models.…”
Section: Introductionmentioning
confidence: 99%